2000
DOI: 10.1002/(sici)1097-4628(20000328)75:13<1577::aid-app3>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on dimensional stability of rat tail tendon collagen fiber

Abstract: The organized molecular structure of collagen is related to its dimensional stability. The dimensional stability of collagen arises from the interplay of various intermolecular forces such as covalent, hydrogen bonding, electrostatic interactions, hydrophobic interactions, London or van der Waals forces, and weak interactions. A structure-function relationship exists in collagen. Electrostatic interactions play an important role in dimensional stabilization. The dimensional stability of rat tail tendon (RTT) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Varying the pH and temperature during gel formation has been shown to affect the structure of collagen gels. Lower pH leads to more compliant materials with decreased fibril diameter [28, 29], possibly due to protonation of the COOH groups and a consequent reduction in interactions between the carboxyl and amino acid groups [30]. Higher temperatures affect the structure of nascent collagen by providing energy to increase the rate of fibrillogenesis and decrease both the diameter of the fibers [31] and the pore size in the meshes [32], which can result in increased mechanical properties [33].…”
Section: 0 - Isolation and Reconstitution Of Collagen Into Hydrogelmentioning
confidence: 99%
“…Varying the pH and temperature during gel formation has been shown to affect the structure of collagen gels. Lower pH leads to more compliant materials with decreased fibril diameter [28, 29], possibly due to protonation of the COOH groups and a consequent reduction in interactions between the carboxyl and amino acid groups [30]. Higher temperatures affect the structure of nascent collagen by providing energy to increase the rate of fibrillogenesis and decrease both the diameter of the fibers [31] and the pore size in the meshes [32], which can result in increased mechanical properties [33].…”
Section: 0 - Isolation and Reconstitution Of Collagen Into Hydrogelmentioning
confidence: 99%
“…The effect of pH on the dimensional stability of RTT collagen fibre has been reported earlier. [36] Role of Solvents…”
Section: Influence Of Ph Conditionsmentioning
confidence: 99%
“…For gelatin gels IEP = 5.6 and for collagen IEP ≃ 7 (Usha and Ramasami, 2000; Highberger, 1939). The observed pH effects on mechanical properties are predominantly elastic, which is consistent with the literature describing how pH can influence the molecular structure of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing or decreasing the pH from the IEP degrades the gelatin molecules, although the amount of degradation is greater for acidic gels (Mohanty et al, 2007), resulting in shorter gelatin fragments. pH adjustments also induce structural changes in collagen (Usha and Ramasami, 2000; Roeder et al, 2002; Seehra and Silver, 2006). Roeder et al (2002) found that an increase in pH produced fibrils of longer length, while a decrease in pH resulted in shorter collagen fibrils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation